2009
DOI: 10.1249/mss.0b013e31819b3607
|View full text |Cite
|
Sign up to set email alerts
|

Central Activation and Force-Frequency Responses of the Lumbar Extensor Muscles

Abstract: Central activation and force-frequency testing of the lumbar extensor muscles is feasible, and the data reported here represent, to our knowledge, the first of their kind in this muscle group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The underlying cause of this phenomenon remains to be elucidated. It is unlikely that it is due to any decreased sensitivity of myofilaments to calcium, because we found that the stimulation frequency for which 50% of the maximum force was exerted—an in vivo indicator of calcium sensitivity (57)—was not affected by sActRIIB‐Fc treatment. On the other hand, it has been established that myostatin deficiency reduces muscle collagen content, thereby altering muscle mechanistic by increasing the stiffness of muscle aponeurosis and tendon (58, 59).…”
Section: Discussionmentioning
confidence: 89%
“…The underlying cause of this phenomenon remains to be elucidated. It is unlikely that it is due to any decreased sensitivity of myofilaments to calcium, because we found that the stimulation frequency for which 50% of the maximum force was exerted—an in vivo indicator of calcium sensitivity (57)—was not affected by sActRIIB‐Fc treatment. On the other hand, it has been established that myostatin deficiency reduces muscle collagen content, thereby altering muscle mechanistic by increasing the stiffness of muscle aponeurosis and tendon (58, 59).…”
Section: Discussionmentioning
confidence: 89%
“…Accumulation of tubular aggregates at the calcium release channel of the sarcoplasmic reticulum has also been proposed to alter calcium handling during excitation-contraction cycles in myostatin-deficient mice, thereby altering mechanical performance (2,9). Nevertheless, this issue remains unlikely herein, because we found that ActRIIB blockade did not affect f 50 (the electrostimulation frequency for which 50% of the maximal tetanic force was exerted), an in vivo indicator of calcium sensitivity (21,54). On the other hand, it is possible that the reduced mechanical capacity in sActRIIB-Fc-treated animals was linked to hypertrophy-induced alterations of fiber pennation angles caused by increased muscle cross-sectional area.…”
Section: Discussionmentioning
confidence: 71%